PREPARASI BENTONIT ALAM MENJADI NANO PARTIKEL - Bukit, Nurdin; Ginting, Eva Marlina; Harahap, Mukti Hamjah (JURNAL PENELITIAN SAINTIKA, 2014)
The purpose of this study is the manufacture of natural bentonite into nano particles and is used as a filer on thermoplastic high-density polyethylene ( HDPE ) . The method used in the manufacture of nanoparticles of bentonite are two ways ; The first synthesis method using surfactant cetyl trimethyl ammonium bromide ( CTAB ) and the second way in ballmill for 10 hours . Characterization of the particle size analyzer ( PSA ) , morphological analysis with scanning electron microscope ( SEM ) and analysis of the structure by X - ray diffraction ( XRD ) was performed . Nano particles with variation of composition of natural bentonite ( 2 , 4 , 6 , 8 , 10 % w t) blends with HDPE and compatibilizer PE - g- MA on the appliance s internal mixer at a temperature of 150oC and laboplatomil rate of 60 rpm for 10 minute.Berdasarkan PSA analysis and X - ray , natural bentonite having an average size of 75 nm for synthesis with CTAB , and 97.5 nm for the ball mill . from the results of XRD analysis of minerals crystoballite ( SiO2 ) and phase annite ( Al3.448Fe3K0.99Na 0.01O12Si 2.552 ) . In testing the mechanical properties of the resulting increase in tensile strength and breaking up the composition perpajangan 2 to 6 % and a decline in the composition of 8 % . The results of SEM analysis showed that homogeneous mixing of ingredients and the bentonite particle agglomeration on the composition of 10 % wt.